Nineteen Years of Japanese Encephalitis Surveillance in Sabah, Malaysian Borneo - Marilyn Charlene Montini Maluda; Jenarun Jelip; Mohd Yusof Ibrahim; Maria Suleiman; Mohammad Saffree Jeffree; Azalina Farina binti Aziz; Jaeyres Jani; Takaaki Yahiro; Kamruddin Ahmed (2020)
Japanese encephalitis (JE) is endemic in Malaysia. Although JE vaccination is practiced in the neighboring state of Sarawak for a long time, little is known about JE in Sabah state in Borneo. As a result, informed policy formulation for JE in Sabah has not been accomplished. In the present study, we have analyzed JE cases that have been reported to the Sabah State Health Department from 2000 to 2018. A total of 92 JE cases were reported during 19 years, and three-fourths of the cases were attributed to children. The estimated mean incidence for JE cases is 0.161/100,000 population. Japanese encephalitis was predominant in Sabah during June, July, and August, peaking in July. In most cases, pigs were absent within a 400-m radius of the place of residence. We could not establish any relationship between the mapping of JE cases and the number of piggeries in each district. We could not establish a relationship between average rainfall and JE cases, either. We propose the cases reported are possibly showing the tip of an iceberg and continuous surveillance is needed, as JE is a public health challenge in Sabah.